Development of The AKM Test With Javanese Cultural Context to Measure Numeracy Literacy Skills In Statistical Materials For High School Student - Mohammad Syaifuddin; Kamilia Rahmah; Retno Wahyu Arian Sah; M Ruskhan Fauza (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
The 2013 curriculum prioritizes 21st century skills, where students are able to be creative and innovate, think critically and problem solving, collaborate, communicate, and literacy skills are also prerequisites for 21st century life skills. The purpose of this study was to develop an AKM test based on Javanese cultural context to measure numeracy literacy skills in high school students' statistical material. This research uses research and development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The type of development in this research is instrument development. The instrument developed is in the form of developing an AKM test instrument based on Javanese culture with the level of the kromo inggil language. The test results on the AKM test instrument based on Javanese culture are valid and reliable